Cancun Accord: Will it be a Reality or Proved to be a Myth? - Iqbal, Badar Alam (Richtmann Publishing, 2011)
Global warming or climate change is the most critical and strategic issue of 21st Century. For the last 25 years i.e. from1985, global warming summits have been taking place. But the real breakthrough has not been come up and the same hasbecome a distant dream. Copenhagen or COP 15 Accord made some head way and as a result, global leaders took note of it.But the same was not considered as a decision and hence, there was no legal binding on the members in respect of cut in globalcarbon dioxide emissions (chart). Keeping in mind the out come of Copenhagen Summit, it was believed that Cancun summitwould give some concrete solution to the problem of global warming or climate change. The Cancun summit out come is mixtureof optimism, consensus and compromises. Therefore, the present paper examines Cancun agreement at a glance and thereasons for optimism, consensus and compromises. The paper also opines whether Cancun Accord would be proved to be areality or otherwise.